DETERMINASI KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU MADRASAH - Sessi Rewetty Riviila; Lathifaturrahmah Lathifaturrahmah; Yusran Fauzi (STKIP Pesisir Selatan, 2026)
Teachers play an important role in the development of human resources. However, based on data obtained from the Teacher Competency Test, the level of basic education in South Kalimantan is still relatively low. This study aims to investigate the factors that influence the pedagogical and professional competencies of Islamic Elementary Schools teachers, as well as determine the strategies used to improve these competencies. The research method used a survey with a quantitative approach, involving 423 respondents selected using a cluster sampling technique. Data were collected through questionnaires and document analysis, then analyzed using Principal Component Analysis. The findings show that factors influencing the pedagogical and professional competencies of MI teachers in South Kalimantan include: (1) welfare/compensation; (2) leadership; (3) work discipline; (4) utilization of information technology; (5) work achievement; (6) learning evaluation; and (7) motivation. As a solution to improve these competencies, this study recommends several strategies including providing incentives in accordance with the regional minimum wage, rewarding outstanding teachers, implementing intensive academic supervision, optimizing the use of information technology, organizing workshops or training, strict selection in the recruitment process of new teachers, and encouraging teachers to improve their work performance.